Pengaruh Penggunaan Digital Supply Chain Platform Terintegrasi Berbasis Fintech dan Logistik serta Financial Self-Efficacy terhadap Keberlanjutan Bisnis UMKM dengan Literasi Digital sebagai Variabel Moderasi - Muhammad Farrel Adi Pratama (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of Digital Supply Chain Platform integrated with Fintech and Logistics and Financial Self-Efficacy on MSME Business Sustainability with Digital Literacy as a moderating variable. The research employs a quantitative explanatory method with 408 e-commerce MSME respondents in the Jabodetabek area. Data analysis uses Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that the use of Digital Supply Chain Platform has a positive and significant effect on MSME Business Sustainability (β=0.295; p<0.001), and Financial Self-Efficacy also has a positive and significant effect (β=0.256; p<0.001). Digital Literacy moderates the relationship between Digital Supply Chain Platform and Business Sustainability (β=0.130; p=0.027), indicating that higher digital literacy strengthens the impact of platform utilization on business sustainability. However, Digital Literacy does not moderate the relationship between Financial Self-Efficacy and Business Sustainability (β=-0.039; p=0.548), suggesting that financial self-efficacy operates autonomously regardless of digital competence. The PLS-SEM model explains 29.5% of the variance in MSME Business Sustainability (R²=0.295) with an SRMR value of 0.032, indicating a very good model fit. This study concludes that business sustainability in the digital era results from the interaction between technological resources, psychological-financial capabilities, and digital competencies that collectively form the foundation of long-term business competitiveness and resilience.